2020
DOI: 10.1111/codi.15279
|View full text |Cite
|
Sign up to set email alerts
|

Enteral stoma care during the COVID‐19 pandemic: practical advice

Abstract: group for STOmas (MISSTO) collaborative members are listed in the Acknowledgement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
8
0
2
Order By: Relevance
“…The COVID-19 pandemic represents an additional challenge [ 29 , 30 ]. The extended wait times for elective surgeries and the backlog caused by the repeated lockdowns during pandemic waves is an unwanted heritage of the SARS-CoV-2 outbreak [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic represents an additional challenge [ 29 , 30 ]. The extended wait times for elective surgeries and the backlog caused by the repeated lockdowns during pandemic waves is an unwanted heritage of the SARS-CoV-2 outbreak [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…After the emergence of COVID-19, the Japanese Society of Stoma and Continence Rehabilitation advocated the guidelines regarding consultation at ostomy clinics; consistent with the recommendation in other countries [ 10 ], they include rethinking of the indications for ostomy clinic visits and seeking alternative methods and risk assessment based on PCR testing of SARS-CoV-2, stoma site, stool form scale, patient posture, zoning of SARS-CoV-2-positive and -negative patients, and additional use of personal protective equipment such as single-use gowns, surgical masks, hair-nets, eye protection, and disposable gloves. Stoma care service at our clinic abides by the abovementioned guidelines.…”
Section: Discussionmentioning
confidence: 92%
“…Zhang et al reported that the virus is detectable in the stool of more than 50% of patients diagnosed with COVID-19 regardless of disease severity, and remains longer in the feces than in the nasopharynx and deep throat [ 9 ]. The Multidisciplinary Italian Study group for STOmas (MISSTO) recommended that follow-up and elective visits to ostomy care clinics be cancelled and/or postponed [ 10 ]. In addition to the behavior of SARS-CoV-2, these precautionary actions can place a higher burden on stoma patients [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Stoma management has to consider as a risk practice for infectious transmission and all caregivers have to pay attention and protect themselves with PPE [14,17]…”
Section: Bowel Anastomosis and Stoma Creationmentioning
confidence: 99%